Narratives of Community Resilience from Two Villages in North Cotabato - Ilagan, Gail T. (Philippine Social Sciences Review; Volume 64, No. 2, July-Dec 2012, Ed. Rolando C. Esteban, 2014)
This study uses narrative psychology and interpretative phenomenological techniques to privilege the subjective meaning locals make in the stories they tell of human-initiated disasters that visited their communities in the last decade. Results yielded the articulation of social imaginaries, community trauma events, and elements of community resilience in the anticipatory processes, coping, protection and functional adjustments, and adaptive learning carried in these narratives. The impact of community disaster is examined in terms of re-organization of thought, social relationships, and community processes that enhance the villagers’ ability to anticipate, withstand, and ward off future such adversities. Findings indicate the need to highlight the importance of reflective and dialogic processes to promote social cohesion and external support to these villages to improve disaster risk reduction, mitigation, and recovery from future such disturbances.
Keywords: community, resilience